Influence of growth hormone on circulating fibroblast growth factor 21 levels in humans. (24th July 2013) - Lundberg, J.; Höybye, C.; Krusenstjerna‐Hafstrøm, T.; Bina, H. A.; Kharitonenkov, A.; Angelin, B.; Rudling, M.
Abstract Objective Findings from animal studies indicate that growth hormone (GH) may stimulate the production of the putative metabolic regulator fibroblast growth factor 21 (FGF21). We investigated whether circulating FGF21 levels are altered in patients with GH deficiency and characterized how levels of this growth factor are influenced by acute and long‐term administration of GH, and the potential relationship between FGF21 and nonesterified fatty acids (NEFAs). Design and setting GH‐deficient patients (n = 9) were studied prior to and during 1 year of replacement with GH. Healthy subjects (n = 8) received an intravenous bolus of GH with or without concomitant oral glucose. Healthy subjects and patients with heterozygous familial hypercholesterolaemia (n = 23) were monitored following increasing doses of GH for 3 weeks. The main outcome measures were serum FGF21 and NEFA levels. Studies were performed at two academic centres. Results GH‐deficient patients had FGF21 levels within the normal range, and GH replacement did not influence circulating FGF21 or NEFA concentrations. Acute GH administration to healthy control subjects did not change FGF21 levels, whereas an oral glucose load increased serum FGF21 by 25% and reduced NEFA levels by 48%. Similar effects were seen on administration of glucose together with GH. However, FGF21 levels increased dose dependently up to 3.7‐fold in control subjects treated with GH for 3 weeks; simultaneously NEFA levels were increased by 47%. Conclusions GH is not critical for the maintenance of basal serum FGF21 levels in humans, but circulating FGF21 levels increase following administration of GH to healthy individuals. There is no correlation between plasma NEFA and circulating FGF21 levels.